A generalization concerning DP-internal ellipsis - Cinque, Guglielmo (IBERIA: An International Journal of Theoretical Linguistics, 2014)
In this article I consider a particular generalization concerning ellipsis within the extended nominal projection: ellipsis can target a nominal modifier only if all constituents below it are also elided. Building on an analysis of ellipsis grounded in movement to left edges, I suggest that this generalization follows from a condition on DP-internal movement proposed in Cinque (2005).